Exploring the Factors Influencing South African Luxury Consumers’ Purchase Decisions in Relation to Genuine and Counterfeit Luxury Goods - Izzard, Gabrielle (The IIE, 2022)
The research paper explores the factors influencing South African (SA) luxury consumers’ purchase decisions in relation to genuine and counterfeit luxury goods. Counterfeiting is recognised as a growing global economic problem, driven in part by consumer demand (International Anti-Counterfeit Coalition, 2021). It is therefore important to understand the factors that may influence luxury consumers’ purchase decisions with regards to genuine and counterfeit luxury goods. The Theory of Planned Behaviour (TPB) (Ajzen, 1991) was used to understand how consumers make purchase decisions in light of their attitudes, social norms and perceived ease or difficulty in performing the desired purchase. The small-scale qualitative study obtained a sample of four SA luxury consumers with counterfeit purchase experiences. A semi-structured, one-on-one interview approach was implemented to gather data from the sample group. Following a thematic analysis, findings indicated that participants’ counterfeit luxury purchases were influenced by social norms of status and superiority, social recognition, novelty seeking attitudes, and easy access and affordability of goods. While their genuine luxury purchases were influenced by social norms relating to status, superiority and social recognition, attitudes relating to personal gratification, self-representation and integrity, and the goods’ timelessness, durability, quality, uniqueness and accessibility. Results from the research are of significance to established luxury brands threatened by the counterfeit market, and suggests that genuine luxury goods be marketed to provide the benefit of timelessness, durability, and high quality. Additionally, findings imply that further research on is required to understand how luxury goods can maintain their uniqueness and scarcity, whilst also maintaining their premium prices, to lessen the threat of counterfeits.
Keywords: Customer behaviour; Buying patterns; Retail